COVID-19 in immunocompromised patients: A systematic review of cancer, hematopoietic cell and solid organ transplant patients. Issue 3 (March 2021) - Belsky, Jennifer A.; Tullius, Brian P.; Lamb, Margaret G.; Sayegh, Rouba; Stanek, Joseph R.; Auletta, Jeffery J.
Highlights: Immunocompromised patients tend to have more comorbidities known to enhance risk of severe COVID-19 than the general population. While the proportion of patients with severe disease does not appear to differ from the general population, mortality and need for intensive care appear to be worse among the immunocompromised. At time of diagnosis, immunocompromised patients are typically lymphopenic, but not leukopenic with elevation of inflammatory markers on par with or exceeding that of the general population with COVID-19. Management of COVID-19 in the immunocompromised frequent involved changes in the management of their underlying disease, which could be deleterious to their disease outcome. Abstract: Background: The clinical impact of severe coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in immunocompromised patients has not been systematically evaluated. Methods: We reviewed current literature reporting on COVID-19 in cancer (CA), hematopoietic cell (HCT), and solid organ transplant (SOT) patients and compared their clinical data and outcomes to the general population. For adult CA, HCT and SOT patients, an extensive search strategy retrieved all articles published until July 20, 2020 by combining the terms coronavirus, coronavirus infection, COVID-19, and SARS-CoV-2 in PubMed, Cochrane, and Web of Science, and following the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. For the pediatric CA cohort, a global COVID-19 registry was used. For the general population cohort, a large meta-analysis was used to compare pooled prevalence estimates, and two large meta-analyses were utilized to serve as pooled comparators for hospitalized COVID-19 patients. Findings: Compared to the general population, adult CA and SOT patients with COVID-19 had higher comorbidities, greater levels of inflammatory markers at diagnosis, and higher rates of intensive care and hospital mortality. Pediatric CA patients and HCT patients with COVID-19 tended to have clinical presentations and outcomes similar to the general population. Interpretation: To our knowledge, this is the first systematic review evaluating COVID-19 phenotype and outcomes in immunocompromised patients and comparing them to the general population, which shows that hospital outcomes appear to be worse in adult CA and SOT patients, potentially due to their higher co-morbidity burden. Funding: None